Endoscopic mucosal resection with anchoring of the snare tip: multicenter retrospective evaluation of effectiveness and safety - Pioche, Mathieu; Wallenhorst, Timothée; Lepetit, Hugo; Lépilliez, Vincent; Rivory, Jérôme; Legros, Romain; Rostain, Florian; Bianchi, Laurent; Charissoux, Aurélie; Hervieu, Valérie; Moreno-Garcia, Maira; Robinson, Philip; Saurin, Jean-Christophe; Ponchon, Thierry; Viprey, Marie; Roche, Laurent; Subtil, Fabien; Jacques, Jérémie (Endoscopy International Open, 2019)
Background Endoscopic mucosal resection (EMR) with snare is the recommended technique to resect non-invasive colorectal neoplastic lesions between 10 and 30 mm in diameter. The objective of EMR is to resect completely the neoplastic tissue en bloc and preferably with free margins (R0), avoiding recurrences. Anchoring the tip of the snare in the submucosa is a technical trick that allows snare sliding to be reduced and larger pieces to be caught. The aim of the present study was to evaluate the effectiveness and safety of anchoring-EMR (A-EMR).Methods This was a retrospective analysis of A-EMR procedures for lesions of diameter between 10 and 30 mm (endoscopic evaluation) performed consecutively in four French centers between May 2017 and January 2018. A-EMR was routinely performed for all EMR using Olympus conventional snares (10 or 25 mm). The primary outcome was evaluation of the proportion of R0 resections.Results A total of 141 A-EMR procedures were performed by 10 operators. Mean lesion size was 19.8 mm. Anchoring was feasible in 96.5 % of cases. There were 81.6 % en bloc resections and 70.2 % R0 resections, with the percentage of procedures decreasing with increasing lesion size (82.8 % < 20 mm, 55.3 % 21 – 30 mm, and 50.0 % > 30 mm, P = 0.002). Complete perforations closed endoscopically occurred in 3/141 cases (2.1 %); none occurred in lesions < 20 mm in size (0 /87).Conclusion The A-EMR technique appears to be promising with a high proportion of R0 for lesions of 10 – 20 mm in size without any perforations. It could also offer an alternative to endoscopic submucosal dissection (ESD), or to hybrid techniques to reach R0 for lesions between 20 and 30 mm in size.